GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU PENDERITA TUBERCULOSIS (TBC) DI WILAYAH KERJA PUSKESMAS BANJARMANGU 1 TAHUN 2023 - Barni; Intan Nurjanah (Jurnal Ilmiah Medsains, 2024)
Tuberculosis or TB is a disease caused by infection of the Mycobacterium tuberculosis bacteria in the lungs. Tuberculosis bacteria that invade the lungs cause respiratory problems, such as chronic cough and shortness of breath. TB disease is included in the 5 environment-based infectious diseases in the working area of Puskesmas Banjarmangu 1 which has many cases. The purpose of this study was to determine the description of knowledge, attitudes and behavior of people with TB in the working area of Puskesmas Banjarmangu 1 in 2023. This study included descriptive research with a cross sectional approach. The study population was 32 respondents with TB. The data used in the study were primary data obtained from direct interviews with a questionnaire guide. Data analysis was carried out in a univariate manner. The results showed that the description of the knowledge of TB patients in the good category was 90.9%, the attitude of TB patients in the good category was 86.4%, and the behavior of TB patients in the poor category was 31.8%.